Triiodothyronine impregnated alginate/gelatin/polyvinyl alcohol composite scaffold designed for exudate-intensive wound therapy. (January 2019) - Satish, Aishwarya; Aswathi, R.; Caroline Maria, J.; Sai Korrapati, Purna
Graphical abstract: Highlights: Alginate based wound dressing that absorbs excess exudates providing a favourable environment for healing. Regulated release of encapsulated bioactive so as to bolster the regeneration process. Scaffold encourages favourable cell interactions promoting cell proliferation and migration. Promotes angiogenesis enabling neovasculature development. Animal experiment validates the potential of the scaffold for enabling effective healing. Abstract: Chronic wound management is challenging and is further intensified due to its increasing prevalence attributed to escalation of ailments like diabetes. Presence of exudates further sustains the chronicity and is a significant burden for the healthcare sector. In this work, a wound dressing material has been formulated in the form of a lyophilized hydrogel comprising of alginate, gelatin and polyvinyl alcohol, with an aim to absorb exudates, maintain a moist environment and enhance interaction with the tissues. Triiodothyronine (active form of thyroid hormone) having vital role in repair and regeneration of tissues is incorporated in the scaffold to bolster the healing process. The fabricated scaffold is physicochemically characterized and the release of hormone has been analysed. The scaffold promotes neovasculature development, skin cell proliferation and migration with cell-biomaterial interaction and lamellipodia formation (observed by phalloidin staining). Animal experiment studies (full-thickness excision wounds created in Wistar rat model) substantiated the explicit potential of the scaffold to encourage faster wound healing. Histological studies further corroborated enhanced healing progression with blood vessel development and collagen deposition. Hence the fabricated scaffold possesses immense potential to be exploited as a chronic wound therapeutic.